Pemanfaatan E-Learning pada Pembelajaran di Prodi PGMI Universitas Islam Negeri Raden Fatah Palembang - Miftahul Husni; Al Ihwanah; Mancar Mancar; Djoko Rohadi Wibowo; Agra Dwi Saputra (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to find out how to use e-learning and the obstacles faced by lecturers and students when using e-learning in the learning process in the third semester of the Madrasah Ibtidaiyah Teacher Education (PGMI) Study Program. This study used a qualitative descriptive research method. The data collection tool was a questionnaire with interviews and observation. Data analysis techniques use Miles and Humberman's theory, namely, data reduction, data display, and drawing conclusions. The results showed the use of e-learning in the learning process in third semester of the PGMI study program was very effective. The data showed that almost all courses use e-learning, only two lecturers with the same subject, namely scouts, who do not use e-learning. The data also showed that 71.8% or 135 students said that e-learning was very effective in learning. The constraints faced by lecturers regarding the use of e-learning were that not all of the features in e-learning exist, for example, lecturer attendance was not yet available, so lecturers have to prepare manually outside of the e-learning application, and virtual face-to-face features of e-learning that were tough to accessed, while the students were more on the capacity limit of uploaded videos.